KONSEP DAN EFEK INTERAKSI DIGITAL KHALAYAK DI MEDIA SOSIAL - Ryan Wahyudi; Anshar, Muhammad; Aldiawan (Rumah Jurnal STAIN Majene, 2024)
In the current digital era, audience behavior in interactions on social media is increasingly complex. The purpose of this article is to analyze the concept and role of audiences in digital interactions on social media. The research method used in this article is library research with a uses and gratifications theory approach. The results of the discussion show that the concept of audience includes; active audience; growing audience; an audience capable of judging; and audiences who are able to take part. Apart from that, this article also covers the motives of audiences for using social media as a media source for disseminating information messages, namely; role effects; and psychological effects. The presence of this article makes it easier for social media communicators to understand in depth the concept of audience, so that the information message distributed can be in line with the communication target. Keywords: audiences, technology and social media. Abstrak Dalam era digital saat ini perilaku khalayak dalam interaksi di media sosial semakin kompleks. Tujuan artikel ini adalah untuk menganalisis konsep dan peran khalayak dalam interaksi digital di media sosial. Metode penelitian yang digunakan dalam artikel ini adalah penelitian pustaka (library research) dengan pendekatan uses and gratifications theory. Hasil pembahasan bahwa konsep khalayak diantaranya; khalayak yang aktif; khalayak yang berkembang; khalayak yang mampu menilai; dan khalayak yang mampu mengambil peran. Selain itu, tulisan ini juga mencakup tentang motif khalayak menggunakan media sosial sebagai sumber media penyebaran pesan informasi, yakni; efek peran; dan efek psikologis. Hadirnya tulisan ini memudahkan komunikator media sosial memahami secara mendalam konsep khalayak, agar pesan informasi yang disebarkan bisa sesuai dengan target komunikasi. Kata Kunci: khalayak, teknologi, dan media sosial.